The effect of colour matching on perceptual integration of pictures and frames. Issue 8 (14th September 2021) - Adler, Harrison; Intraub, Helene
ABSTRACT: A black frame presented around one of 12 pictures during rapid serial visual presentation (RSVP) was frequently misperceived as surrounding the preceding or following picture in the sequence ( temporal migration ; Intraub, 1985, 1989 ). Would temporal migration of the frame be reduced if the frame and picture shared a common property (colour)? Two different colour frames were created for each picture: one matching and one mismatching the picture's most prevalent colour (Experiment 1) as determined by a computational image colour summarizer (Krzywinski, 2018 ). Presentation rate was 100 ms/picture. Colour-matching significantly reduced temporal migration (4.3%), but the effect was small. To determine if greater colour-overlap would yield a larger effect, frames composed of colour "tiles" that matched or mismatched each picture's four most prevalent colours were presented at a rate of 111 ms/picture (Experiment 2). Again, a small, significant reduction in temporal migration was observed (3.2%). Although pictures and frames are distinct forms, the probability of correct integration of the two appears to be affected by the presence of a common property (colour). Results are discussed in terms of an integrative short-term buffer. Possible application of the temporal migration paradigm to studying visual integration of components of real-world scenes is addressed.